高速齿轮轴失效原因分析 - 李妍缘; 赵兴明; 郭宏亮 (Jixie chuandong)
The gear shaft of material 17CrNiMo6 in gear reducer occurs to fretting,stress concentration,fatigue cracking. fatigue breakage produces when the reducer operates 6000 hours. The breakage is normal fatigue breakage with unidirectinal bending and twisting moments. After the fatigue breakage causes are analysized,speafic improving measures are put forward. The good result is achieved.